FOX, Kate. 2004. Watching the English - The Hidden Rules of English Behaviour. London: Hodder and Stoughton Ltd. 424 pp. - Ferreira Pires, Flávia (Campos - Revista de Antropologia, 2006)
Resenha do livro Watching the English - The Hidden Rules of English Behaviour, de Kate Fox, publicado em 2004.